EZ Plate: a tool in evaluating educational program - Nasrudin, Norfadhilah; Abd Rahman, Normarina; Nordin, Hani Syazillah; Muhammad Nasir, Abdul Wahib; Megat Rasidin, Norlelawati; Ramli, Azhari; Ramly, Farah Hanum; Abdul Sidek, Surayni (Academica Press Solutions, 2023)
Education leaders need to proactively evaluate all programs planned and implemented in schools. The practice of program evaluation helps the process of improvement, revision, modification and risk planning on the implemented program. Despite the important benefits of evaluating programs, many program coordinators often are reluctant to evaluate their programs. The reluctance usually stems from a lack of understanding of the program evaluation process especially when they perceive evaluation as being too difficult, complicated and burdensome. Accordingly, school leaders and program coordinators need to be well equipped and properly trained with the knowledge and skills of the evaluation process. It is crucial in determining the effectiveness, efficiency, cost-effectiveness and cost-benefit of the program. Therefore, EZ PLATE intends to assist the school leaders’ in conducting program evaluation in their schools. The objective of the template is to guide leaders regarding real evaluation processes which require immediate feedback on the effectiveness in achieving the program’s objectives. The novelty of this template is that it is designed to allow evaluation, data analysis and reporting of the program’s findings in a much shorter time frame. The template could also be utilized by other stakeholders such as auditors, decision-makers, heads of departments, top management leaders and heads of training units. Data can be shared and used as a benchmark for other functions such as program performance evaluation, individual competency evaluation and re-use by external agencies anytime, fast and accurately. By referring to the template, one can foster best practices in evaluating educational programs effectively and efficiently.